2017
DOI: 10.1016/j.urolonc.2017.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Is restaging transurethral resection necessary in patients with non-muscle invasive bladder cancer and limited lamina propria invasion?

Abstract: Objectives To evaluate the influence of lamina propria invasion type at initial transurethral resection (TUR) on re-staging pathology. Materials and Methods We reviewed prospectively-maintained records of all patients with a high-grade pT1 non-muscle invasive bladder cancer (NMIBC) who underwent both initial and restaging TUR within 6 weeks at our center between 2001 and 2016. The pathology of second TUR specimens was analyzed with regard to the characteristics of lamina propria invasion found at initial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In our study, one-third of patients had minimal lamina propria invasion, which is comparable to previously published data [12]. The prognostic importance of T1 substaging is currently investigated [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, one-third of patients had minimal lamina propria invasion, which is comparable to previously published data [12]. The prognostic importance of T1 substaging is currently investigated [13].…”
Section: Discussionsupporting
confidence: 90%
“…The prognostic importance of T1 substaging is currently investigated [13]. In our cohort, minimal lamina propria invasion was not associated with the second resection outcome, supporting previous findings [12].…”
Section: Discussionsupporting
confidence: 89%
“…Bearing in mind the previous reports, the presented results and the risk of tumour underdiagnosis, we believe that T1 cancers with both focal and massive lamina propria infiltration should undergo reTURB [27, 28]. Additionally, because of poor prognosis rates and safety profile of adjuvant procedures, radical treatment should be considered, especially when massive infiltration was found [2932].…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, Gontero et al [15] reported even a higher rate (30.9%) in a multicenter international study. Recently, a prospective study that included 198 patients with T1 HG/G3 also showed that 1/4 of patients have T1 HG/G3 on re-TUR; they also demonstrated that extent of T1 invasion did not eliminate the need for re-TUR [24].…”
Section: Discussionmentioning
confidence: 99%